The Correlation between Coach-Athlete Relationship and Motivation among Universiti Teknologi Mara (UiTM) Shah Alam Athletes - Nur Amirah, Zaker (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe